Preparation method and application of titanium dioxide supported platinum-copper diatomic catalyst
By mixing platinum and copper atomic levels on titanium dioxide nanoscopy, high -efficiency titanium dioxide can be carried with platinum and copper dual -atomic catalysts, which solves the problem of unsatisfactory performance of cathode materials in the seawater electrolyte. Hydrogen analysis of hydrogen.
Patent Information
- Application Number
- CN202411467093.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The existing technology has high concentrations of corrosive ions and calcium deposits in seawater electrolysis, resulting in unsatisfactory performance of cathode materials and hindering the large-scale application of seawater electrolysis.
Through the "doping-stripping" method, the atomic-level doping of platinum and copper atoms on titanium dioxide nanosheets is controlled to prepare a titanium dioxide-loaded platinum-copper diatomic catalyst, which maximizes the utilization of platinum-copper atoms and improves the efficiency of the catalyst.
Under seawater conditions, the prepared catalysts show the performance of high -efficiency hydrogen performed hydrogen, low potential, small tafel slope, good electrode stability, and broad application prospects.
Smart Images

Figure CN119332289A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysis, and specifically relates to a preparation method and application of a titanium dioxide-supported platinum-copper diatomic catalyst. Background Art
[0002] Hydrogen is a clean and efficient new energy source and an ideal green energy source to replace fossil fuels. Among the many hydrogen production methods, electrochemical water splitting is one of the most promising energy conversion technologies. Because it can not only produce high-purity hydrogen, but also does not emit any greenhouse gases. In the context of water electrolysis, the overall catalytic activity can be improved by optimizing the catalyst and the electrolysis environment. However, the current commercial water electrolysis technology mainly relies on freshwater resources, which may lead to water shortages. In addition, global seawater resources are abundant and have strong sustainability. Direct seawater splitting may be the most practical solution for water electrolysis. However, the biggest challenge of direct seawater splitting is the presence of high concentrations of chloride ions (corrosive ions) and cations (calcium deposits), as well as the low efficiency and slow reaction kinetics of the electrolysis system under near-neutral conditions (~pH 8.0), which leads to unsatisfactory performance of the cathode material, seriously hindering its large-scale application in seawater electrolysis. In summary, the development of an efficient, green and low-cost hydrogen evolution catalyst has extremely important economic value and broad application prospects for the entire hydrogen production industry.
[0003] Therefore, it is of great significance to develop a preparation method for titanium dioxide-supported platinum-copper diatomic catalyst. Summary of the invention
[0004] Among the existing electrocatalytic hydrogen evolution methods, platinum-based catalysts are widely used in hydrogen evolution reactions due to their excellent performance. Despite their high cost, their efficient catalytic performance and stability make them irreplaceable in many high-end applications. Therefore, the use of the above-mentioned electrocatalysts with low platinum dosage, high platinum atomic utilization efficiency and low overpotential is crucial to the current and future hydrogen-driven economy.
[0005] The technical problem to be solved by the present invention is to provide a titanium dioxide-supported platinum-copper diatomic catalyst (Pt x Cu1–TiO2), preparation method and application thereof. The present invention regulates the atomic-level doping of platinum and copper atoms on titanium dioxide nanosheets through the "doping-stripping" method, maximizes the utilization of platinum and copper atoms, and the obtained diatomic platinum and copper doped titanium dioxide nanosheet catalyst can drive efficient hydrogen evolution under seawater conditions.
[0006] In order to solve the above technical problems, the present invention discloses a method for preparing a titanium dioxide-supported platinum-copper diatomic catalyst, the specific steps of which are:
[0007] S1. The hydrochloric acid solution and the tetrabutyl titanate solution were mixed to obtain a mixed solution which was added to an autoclave, heated and kept warm;
[0008] S2. After the autoclave is cooled to room temperature, the product is collected, washed, peeled, centrifuged, and dried to obtain a single-layer titanium dioxide nanosheet;
[0009] S3. The titanium dioxide nanosheets are treated with Ar plasma and then dispersed in deionized water to obtain titanium dioxide colloid;
[0010] S4. After uniformly mixing the ethylenediamine copper solution and the chloroplatinic acid solution, add the mixture to the titanium dioxide colloid obtained in S5, and obtain the titanium dioxide-supported platinum-copper diatomic catalyst through centrifugation and drying.
[0011] The volume ratio of the hydrochloric acid solution to the tetrabutyl titanate solution is 1:(7-9); the concentration of the hydrochloric acid solution is 2-4wt%.
[0012] Wherein, in said S1, during the insulation process, the temperature is controlled to be maintained at 180-200°C for 20-24 hours.
[0013] Wherein, in said S3, the treatment time in the Ar plasma treatment process is 30-40s, and the power is 100-120W.
[0014] Wherein, in S3, the solid-liquid ratio of titanium dioxide nanosheets to deionized water is 1g: (250-300)mL
[0015] The concentration of the chloroplatinic acid solution is 0.009-0.04 wt %; the solid-liquid ratio of the titanium dioxide nanosheets treated with Ar plasma, the ethylenediamine copper solution and the chloroplatinic acid is 1 g: 100 mL: 125 mL;
[0016] Preferably, the concentration of the chloroplatinic acid solution is 0.009-0.01 wt %.
[0017] Specifically, in the titanium dioxide-supported platinum-copper diatomic catalyst prepared by the above preparation method of the present invention, platinum and copper are doped in the titanium dioxide nanosheet layer in the form of diatoms, the doping ratio is 0.5-4wt%, and the thickness of the titanium dioxide nanosheet is 1-1.4nm.
[0018] Specifically, in some embodiments of the present invention, the titanium dioxide-supported platinum-copper diatomic catalyst prepared by the above-mentioned preparation method of the present invention is prepared into a catalyst slurry, and the catalyst slurry is added dropwise onto carbon paper to prepare a working electrode, and then the working electrode is subjected to an electrochemical hydrogen evolution test in a single electrolytic cell, thereby verifying the application prospect of the titanium dioxide-supported platinum-copper diatomic catalyst prepared by the present invention in the field of direct hydrogen production by electrolysis of seawater;
[0019] Preferably, the specific application method is: using seawater as an electrolyte, adding titanium dioxide-supported platinum-copper diatomic catalyst, and performing an electrocatalytic hydrogen evolution reaction at room temperature to produce hydrogen.
[0020] Beneficial effects:
[0021] Compared with pure titanium dioxide nanosheet catalyst, under the same catalytic conditions, Pt x The Cu1–TiO2 nanosheet catalyst exhibits excellent hydrogen evolution performance. Compared with the reported catalysts of the same type, under the same catalytic conditions (seawater), the hydrogen evolution overpotential of Pt1Cu1–TiO2 is 160 mV and the Tafel slope is 77.46 mV dec. –1 , and the electrode exhibited excellent stability during chronoamperometric measurements. x Cu1–TiO2 nanosheet catalysts have broad application prospects in the field of seawater hydrogen evolution. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0023] Figure 1 This is an atomic force microscope (AFM) image of the Pt1Cu1–TiO2 nanosheet catalyst in Example 1 of the present invention;
[0024] Figure 2 The transmission electron microscope (TEM) image and high-resolution electron microscope image (HRTEM) image of the Pt1Cu1–TiO2 nanosheet catalyst in Example 1 of the present invention are shown;
[0025] Figure 3 This is a high-angle annular dark field scanning electron microscope (HAADF-STEM) image of the Pt1Cu1–TiO2 nanosheet catalyst in Example 1 of the present invention;
[0026] Figure 4 The linear sweep voltammogram (LSV) curves of electrochemical hydrogen evolution using the titanium dioxide-supported platinum-copper diatomic nanosheets, titanium dioxide nanosheets and platinum-carbon prepared in Example 1 of the present invention as catalysts. DETAILED DESCRIPTION
[0027] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0028] Embodiment 1:
[0029] The titanium dioxide-supported platinum-copper diatomic catalyst of the present invention has a chemical formula of Pt1Cu1–TiO2 and is prepared by the following method, comprising the following steps:
[0030] (1) Add 3 mL of hydrochloric acid (2-4 wt%) to 25 mL of tetrabutyl titanate solution (platinum strontium titanium; Aladdin; CAS number: 5593-70-4), and stir continuously for 10 minutes to obtain a mixed solution;
[0031] (2) The resulting mixed solution was stored in a 46 mL autoclave at 180°C for 24 h;
[0032] (3) After the sample was cooled to room temperature in the autoclave, the prepared sample was collected and washed with deionized water and anhydrous ethanol respectively. Thiobarbituric acid (TBA) was added to the washed sample and then placed in a shaker for 10 to 15 days. The obtained sample was then centrifuged and dried in an oven at 60°C for 6 hours to obtain a TiO2 sample;
[0033] (4) treating the obtained TiO2 nanosheets with Ar plasma to produce oxygen vacancies, wherein the plasma treatment time is 30 to 40 seconds and the power is 100 to 120 W;
[0034] (5) The obtained TiO2 sample rich in oxygen vacancies was heated to 4 mg mL –1 The solid-to-liquid ratio is then dispersed into water;
[0035] (6) Dissolve 0.48 mg of chloroplatinic acid in 5 mL of deionized water and mix well. Mix it with 4 mL of ethylenediamine copper solution (platinum strontium titanium; Aladdin; CAS number: 14552-35-3). After stirring thoroughly, add it dropwise to 10 mL of TiO2 colloid. The dropping speed is controlled to drop 10 μL every 10 seconds. Finally, centrifuge and freeze-dry to obtain the Pt1Cu1–TiO2 nanosheet catalyst.
[0036] Embodiment 2:
[0037] The titanium dioxide-supported platinum-copper diatomic catalyst of the present invention has a chemical formula of Pt2Cu1–TiO2 and is prepared by the following method, comprising the following steps:
[0038] (1) Add 3 mL of hydrochloric acid (2-4 wt%) to 25 mL of tetrabutyl titanate solution (platinum strontium titanium; Aladdin; CAS number: 5593-70-4), and stir continuously for 10 minutes to obtain a mixed solution;
[0039] (2) The resulting mixed solution was stored in a 46 mL autoclave at 180°C for 24 h;
[0040] (3) After the sample was cooled to room temperature in the autoclave, the prepared sample was collected and washed with deionized water and anhydrous ethanol respectively. After adding TBA to the washed sample, it was placed in a shaker for 10 to 15 days, and then the obtained sample was centrifuged and dried in an oven at 60°C for 6 hours to obtain a TiO2 sample;
[0041] (4) treating the obtained TiO2 nanosheets with Ar plasma to produce oxygen vacancies, wherein the plasma treatment time is 30 to 40 seconds and the power is 100 to 120 W;
[0042] (5) The obtained TiO2 sample rich in oxygen vacancies was heated to 4 mg mL –1 The solid-to-liquid ratio is then dispersed into water;
[0043] (6) Dissolve 0.96 mg of chloroplatinic acid in 5 mL of deionized water and mix well. Mix the mixture with 4 mL of ethylenediamine copper solution (platinum strontium titanium; Aladdin; CAS No.: 14552-35-3). After sufficient stirring, add the mixture dropwise to 10 mL of TiO2 colloid. The addition rate is controlled to drip 10 μL every 10 seconds. Finally, centrifuge and freeze-dry to obtain the Pt2Cu1–TiO2 nanosheet catalyst.
[0044] Embodiment 3:
[0045] The titanium dioxide-supported platinum-copper diatomic catalyst of the present invention has a chemical formula of Pt3Cu1–TiO2 and is prepared by the following method, comprising the following steps:
[0046] (1) Add 3 mL of hydrochloric acid (2-4 wt%) to 25 mL of tetrabutyl titanate solution (platinum strontium titanium; Aladdin; CAS number: 5593-70-4), and stir continuously for 10 minutes to obtain a mixed solution;
[0047] (2) The resulting mixed solution was stored in a 46 mL autoclave at 180°C for 24 h;
[0048] (3) After the sample was cooled to room temperature in the autoclave, the prepared sample was collected and washed with deionized water and anhydrous ethanol respectively. After adding TBA to the washed sample, it was placed in a shaker for 10 to 15 days, and then the obtained sample was centrifuged and dried in an oven at 60°C for 6 hours to obtain a TiO2 sample;
[0049] (4) treating the obtained TiO2 nanosheets with Ar plasma to produce oxygen vacancies, wherein the plasma treatment time is 30 to 40 seconds and the power is 100 to 120 W;
[0050] (5) The obtained TiO2 sample rich in oxygen vacancies was heated to 4 mg mL–1 The solid-to-liquid ratio is then dispersed into water;
[0051] (6) Dissolve 1.44 mg of chloroplatinic acid in 5 mL of deionized water and mix well. Mix the mixture with 4 mL of ethylenediamine copper solution (platinum strontium titanium; Aladdin; CAS No.: 14552-35-3). After sufficient stirring, add the mixture dropwise to 10 mL of TiO2 colloid. The addition rate is controlled to drip 10 μL every 10 seconds. Finally, centrifuge and freeze-dry to obtain the Pt3Cu1–TiO2 nanosheet catalyst.
[0052] Embodiment 4:
[0053] The titanium dioxide-supported platinum-copper diatomic catalyst of the present invention has a chemical formula of Pt4Cu1–TiO2 and is prepared by the following method, comprising the following steps:
[0054] (1) Add 3 mL of hydrochloric acid (2-4 wt%) to 25 mL of tetrabutyl titanate solution (platinum strontium titanium; Aladdin; CAS number: 5593-70-4), and stir continuously for 10 minutes to obtain a mixed solution;
[0055] (2) The resulting mixed solution was stored in a 46 mL autoclave at 180°C for 24 h;
[0056] (3) After the sample was cooled to room temperature in the autoclave, the prepared sample was collected and washed with deionized water and anhydrous ethanol respectively. After adding TBA to the washed sample, it was placed in a shaker for 10 to 15 days, and then the obtained sample was centrifuged and dried in an oven at 60°C for 6 hours to obtain a TiO2 sample;
[0057] (4) treating the obtained TiO2 nanosheets with Ar plasma to produce oxygen vacancies, wherein the plasma treatment time is 30 to 40 seconds and the power is 100 to 120 W;
[0058] (5) The obtained TiO2 sample rich in oxygen vacancies was heated to 4 mg mL –1 The solid-to-liquid ratio is then dispersed into water;
[0059] (6) Dissolve 1.92 mg of chloroplatinic acid in 5 mL of deionized water and mix well. Mix the mixture with 4 mL of ethylenediamine copper solution (platinum strontium titanium; Aladdin; CAS No.: 14552-35-3). After sufficient stirring, add the mixture dropwise to 10 mL of TiO2 colloid. The addition rate is controlled to be 10 μL per 10 seconds. Finally, centrifuge and freeze-dry to obtain the Pt4Cu1–TiO2 nanosheet catalyst.
[0060] Comparative Example 1:
[0061] A method for preparing a metal-free single-layer titanium dioxide nanosheet comprises the following steps:
[0062] (1) Add 3 mL of hydrochloric acid (2-4 wt%) to 25 mL of tetrabutyl titanate solution (platinum strontium titanium; Aladdin; CAS number: 5593-70-4), and stir continuously for 10 minutes to obtain a mixed solution;
[0063] (2) The resulting mixed solution was stored in a 46 mL autoclave at 180°C for 24 h;
[0064] (3) cooling the samples to room temperature in an autoclave, and then collecting the prepared samples and washing them with deionized water and anhydrous ethanol respectively;
[0065] (4) Finally, TBA was added to the washed sample and the sample was shaken in a shaker for 10 to 15 days. The obtained sample was then centrifuged and dried in an oven at 60° C. for 6 h to obtain a TiO2 sample.
[0066] Morphology test: The titanium dioxide-supported platinum-copper diatomic catalyst obtained in Example 1 was tested for microscopic morphology by atomic force microscopy and transmission electron microscopy, wherein: Figure 1 This is an atomic force microscope (AFM) image of the Pt1Cu1–TiO2 nanosheet catalyst; Figure 2 Transmission electron microscopy (TEM) images and high-resolution electron microscopy (HRTEM) images of Pt1Cu1–TiO2 nanosheet catalysts; Figure 3 This is a high-angle annular dark-field scanning electron microscopy (HAADF-STEM) image of the Pt1Cu1–TiO2 nanosheet catalyst;
[0067] pass Figure 1 It can be seen that the atomic force microscope (AFM) of Example 1 observed that the titanium dioxide-supported platinum-copper diatomic catalyst was a single-layer nanosheet structure with a thickness of 1.115 nm.
[0068] pass Figure 2 It can be seen from the transmission electron microscopy (TEM) image of Example 1 that the morphology of the obtained Pt1Cu1–TiO2 nanosheets is almost transparent, and the lattice spacing is 1.96 Å, corresponding to the (200) plane of titanium dioxide, confirming that Figure 1 Discovery in atomic force microscopy (AFM).
[0069] pass Figure 3It can be seen from the HAADF-STEM image of Example 1 that the Pt atoms and Cu atoms in Pt1Cu1–TiO2 are loaded on TiO2 in the form of atomic pairs, indicating that the titanium dioxide-supported platinum-copper diatomic catalyst was successfully synthesized.
[0070] Electrochemical test: 4.8 mg of the titanium dioxide nanomaterials prepared in Examples 1 to 4 and Comparative Example 1 were dispersed in 300 μL of ethanol, 30 μL of Nafion (D520, 5 wt%) solution was added, and 300 μL of deionized water was added after ultrasonic treatment for 20 min, and then ultrasonic treatment was continued for another 20 min to form a uniformly dispersed catalyst slurry. 10 μL of the above catalyst slurry was dripped onto a 0.3 cm –2 Dry on carbon paper, once on the front and once on the back.
[0071] A single electrolytic cell was used for the electrochemical hydrogen evolution test, where the working electrode (cathode) was carbon paper loaded with catalyst, the reference electrode was a silver chloride electrode, and the counter electrode was a carbon rod; a 0.5M Na2SO4 (30mL) solution was placed in the single electrolytic cell. At room temperature, the linear sweep voltammogram (LSV) curve of the catalyst was tested, and the voltage test range was -0.1V to -0.75V (reversible hydrogen electrode potential).
[0072] pass Figure 4 It can be seen that the Pt1Cu1-TiO2 prepared in Example 1 has the best electrocatalytic hydrogen evolution performance in seawater, and its overpotential is much lower than that of the Pt / C catalyst. The catalysts prepared in Examples 1 to 4 and Comparative Example 1 were applied to the electrocatalytic hydrogen evolution reaction in seawater, and the catalytic performance is shown in Table 1. As can be seen from Table 1, the Pt1Cu1-TiO2 doped with different Pt contents has the best electrocatalytic hydrogen evolution performance in seawater, and its overpotential is much lower than that of the Pt / C catalyst. x The electrocatalytic hydrogen evolution performance of the Cu1-TiO2 nanosheet catalysts showed obvious differences. The overpotential of the Pt1Cu1-TiO2 nanosheet catalyst in Example 1 was as low as 160 mV, while the overpotential of the TiO2 nanosheet catalyst in Comparative Example 1 was as high as 830.4 mV.
[0073] Table 1 is a comparison of the performance of electrocatalytic hydrogen evolution of titanium dioxide nanosheets in Examples 1 to 4 and Comparative Example 1
[0074] catalyst <![CDATA[Overpotential (η 10 )]]> Example 1 160 Example 2 174.8 Example 3 182.2 Example 4 189.9 Comparative Example 1 830.4
[0075] The present invention provides a method for preparing a titanium dioxide-supported platinum-copper diatomic catalyst and a method for its application. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A method for preparing a titanium dioxide-supported platinum-copper diatomic catalyst, characterized in that: The specific steps are: S1. The hydrochloric acid solution and tetrabutyl titanate were mixed to obtain a mixed solution which was added to an autoclave, heated and kept warm; S2. After the autoclave is cooled to room temperature, the product is collected, washed, peeled, centrifuged, and dried to obtain a single-layer titanium dioxide nanosheet; S3. The titanium dioxide nanosheets are treated with Ar plasma and then dispersed in deionized water to obtain titanium dioxide colloid; S4. After uniformly mixing the ethylenediamine copper and chloroplatinic acid solutions, add the mixture to the titanium dioxide colloid obtained in S3, and obtain the titanium dioxide-supported platinum-copper diatomic catalyst after centrifugation and drying.
2. The preparation method according to claim 1, characterized in that: The volume ratio of the hydrochloric acid solution to tetrabutyl titanate is 1:(7-9); the concentration of the hydrochloric acid solution is 2-4wt%.
3. The preparation method according to claim 1, characterized in that: In S1, the temperature is controlled to be maintained at 180-200° C. during the insulation process for 20-24 hours.
4. The preparation method according to claim 1, characterized in that: In the S3, the Ar plasma treatment process has a treatment time of 30 to 40 seconds and a power of 100 to 120W.
5. The preparation method according to claim 1, characterized in that: In S3, the solid-liquid ratio of titanium dioxide nanosheets to deionized water is 1 g: (250-300) mL.
6. The preparation method according to claim 1, characterized in that: The concentration of the chloroplatinic acid solution is 0.009-0.04wt%; the solid-liquid ratio of the titanium dioxide nanosheets, copper ethylenediamine and chloroplatinic acid after Ar plasma treatment is 1g:100mL:125mL.
7. The titanium dioxide-supported platinum-copper diatomic catalyst prepared by the preparation method according to any one of claims 1 to 6.
8. The catalyst according to claim 7, characterized in that In the titanium dioxide-supported platinum-copper diatomic catalyst, platinum-copper is doped in the titanium dioxide nanosheet layer in the form of diatoms, the doping ratio is 0.5-4wt%, and the thickness of the titanium dioxide nanosheet is 1-1.4nm.
9. Use of the catalyst according to claim 7 in the field of direct hydrogen production by seawater electrolysis.
10. The use according to claim 9, characterized in that: The specific application method is: using seawater as an electrolyte, adding titanium dioxide-supported platinum-copper diatomic catalyst, and performing an electrocatalytic hydrogen evolution reaction at room temperature to produce hydrogen.
Citation Information
Patent Citations
Preparation method of load bimetal type Cu-Pt / TiO2-NBs catalyst and application
CN104549368A
Preparation and application of monatomic uranium-titanium dioxide catalyst for synthesizing ammonia through electro-catalysis of nitrogen
CN115261923A
Preparation method and application of Cu-TiO2-x electro-catalytic material
CN117947455A